Analisis Kebutuhan Pendidikan Pencegahan Perilaku Berisiko pada Remaja di Kabupaten Magelang - Silmi, Fina Idamatus (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Adolescents are vulnerable to risky behaviors such as smoking, alcohol consumption, and risky sexual behavior. The involvement of one risky behavior can lead to other risky behaviors. Therefore, it is necessary to prevent risky behavior to ensure adolescents' health. This study aimed to prevent risky behaviors according to adolescents' needs.Method: This was an observational research with the cross-sectional method. Data were obtained using a questionnaire through interviews with respondents. The research subjects were adolescents aged 15-24 years. Samples were randomly selected, as much as 100 adolescents. Results: There were 2 categories of adolescents, they were "delinquent adolescents" and "ordinary adolescents". The needs of SRH education of two groups were more in contents of  SRH,  methods, media, time, providers, and venue of SRH information delivery. The majority of respondents mostly preferred to select the subject related to he impact of risky behaviour.  Discussion method and mixed media, they like to choose for delivering information at night time. Most of them prefer health workers to be as health educator beside their peers. There was no significant difference in the SRH need between two groups. However, the implementation of risky behavior prevention should be differentiated.